Gambaran Sanitasi Gereja Masehi Injili di Timor (GMIT) di Wilayah Kecamatan Kelapa Lima Kota Kupang - Stella Lebrina Manoe; Mustakim Sahdan; Cathrin W. D. Geghi (Yayasan Literasi Sains Indonesia, 2025)
Public place sanitation requires serious attention because it is a gathering place for many people from various backgrounds. With the majority of Kupang City's population being Christian, churches, as places of worship, are one of the public places whose sanitation needs attention, especially those located in the Kelapa Lima District. Kelapa Lima District is located near the coast, making it prone to flooding and strong winds, which can damage church facilities and disrupt their sanitation. The purpose of this study was to determine the sanitation of the church environment and buildings, as well as its sanitation facilities. This research is a descriptive study using an observational checklist method based on the Church Inspection Form stipulated by Decree of the Minister of Health 288/MENKES/SK/III/2003 concerning Guidelines for the Sanitation of Public Facilities and Buildings. The results indicate that all Evangelical Christian Churches in Timor (GMIT) in the Kelapa Lima District meet environmental and building sanitation requirements with a score of 70% or more and meet sanitation facility requirements with a score of 75%. However, several churches do not meet the requirements for certain variables, such as yard sanitation, toilets, trash cans, and worship equipment. Churches are expected to pay special attention to church sanitation by establishing a regular cleaning schedule, such as washing offering trays and routinely cleaning church toilets, not only on Sundays but also every two weeks.